The role of mangroves in supporting shipping industry commitments to environmental protection and sustainable development - Pham Thu Thuy; Nguyễn Thị, V.A.; Nguyễn Thị, T.A.; Tăng Thị, K.H.; Đặng, H.P.; Nguyễn Thị, K.N.; Đặng, L.H.; Phạm, T. Thuyền; Hoàng, T.L. (Center for International Forestry Research, 2021)
Due to the increasing speed and impacts of climate change, the United Nations Framework Convention on Climate Change (UNFCCC) and countries around the world are calling for active participation from all sectors in helping to resolve global environmental problems. The shipping industry, which plays a leading role in world commerce by transporting 90% of goods globally, has the potential to contribute significantly in the battle to adapt to and mitigate the impacts of climate change.